From peculiar morphologies to Hubble-type spirals: the relation between galaxy dynamics and morphology in star-forming galaxies at z ∼ 1.5. Issue 1 (23rd December 2019) - Gillman, S; Tiley, A L; Swinbank, A M; Harrison, C M; Smail, Ian; Dudzevičiūtė, U; Sharples, R M; Cortese, L; Obreschkow, D; Bower, R G; Theuns, T; Cirasuolo, M; et al.
ABSTRACT: We present an analysis of the gas dynamics of star-forming galaxies at z ∼ 1.5 using data from the KMOS Galaxy Evolution Survey. We quantify the morphology of the galaxies using HST candels imaging parametrically and non-parametrically. We combine the H α dynamics from KMOS with the high-resolution imaging to derive the relation between stellar mass ( M * ) and stellar specific angular momentum ( j * ). We show that high-redshift star-forming galaxies at z ∼ 1.5 follow a power-law trend in specific stellar angular momentum with stellar mass similar to that of local late-type galaxies of the form j * ∝ M $_*^{0.53\, ± \, 0.10}$ . The highest specific angular momentum galaxies are mostly disc-like, although generally both peculiar morphologies and disc-like systems are found across the sequence of specific angular momentum at a fixed stellar mass. We explore the scatter within the j * – M * plane and its correlation with both the integrated dynamical properties of a galaxy (e.g. velocity dispersion, Toomre Qg, H α star formation rate surface density ΣSFR ) and its parametrized rest-frame UV / optical morphology (e.g. Sérsic index, bulge to total ratio, clumpiness, asymmetry, and concentration). We establish that the position in the j * – M * plane is strongly correlated with the star-formation surface density and the clumpiness of the stellar light distribution. Galaxies with peculiar rest-frame UV / optical morphologies have comparable specific angular momentum to disc- dominated galaxies of the same stellar mass, but are clumpier and have higher star formation rate surface densities. We propose that the peculiar morphologies in high-redshift systems are driven by higher star formation rate surface densities and higher gas fractions leading to a more clumpy interstellar medium.